2017
DOI: 10.1111/cdev.12973
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded View of Joint Attention: Skill, Engagement, and Language in Typical Development and Autism

Abstract: This study provides an expanded view of joint attention and its relation to expressive language development. A total of 144 toddlers (40 typically developing, 58 with autism spectrum disorder [ASD], 46 with developmental delay [DD]) participated at 24 and 31 months. Toddlers who screened positive for ASD risk, especially those subsequently diagnosed with ASD, had poorer joint attention skills, joint engagement during parent-toddler interaction, and expressive language. Findings highlight the dynamic relation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 50 publications
(88 reference statements)
1
87
1
5
Order By: Relevance
“…Children diagnosed with autism also show reduced joint attention during infancy and are impaired in their ability to use others' gaze cues in word learning tasks (Franchini et al, 2019). It is reported that early joint attention abilities are predictive of later language functioning and communication abilities in autism (Adamson et al, 2019;Dawson et al, 2004;Poon et al, 2012). Therefore, if early joint attention can be enhanced in children with autism at a young age, it may reduce later language impairments and improve communication.…”
Section: Communication Deficits As a Core Symptom Of Autismmentioning
confidence: 99%
“…Children diagnosed with autism also show reduced joint attention during infancy and are impaired in their ability to use others' gaze cues in word learning tasks (Franchini et al, 2019). It is reported that early joint attention abilities are predictive of later language functioning and communication abilities in autism (Adamson et al, 2019;Dawson et al, 2004;Poon et al, 2012). Therefore, if early joint attention can be enhanced in children with autism at a young age, it may reduce later language impairments and improve communication.…”
Section: Communication Deficits As a Core Symptom Of Autismmentioning
confidence: 99%
“…Joint attention is an early-developing social communicative skill where two people use gestures and gaze to share attention with respect to interesting objects or events. It plays a vital role in social and language development [12,21]. Children with ASD spent less time gazing at the eyes of the human face and at the pointed object by the teacher and spent more time gazing at irrelevant areas, such as a pencil case on a desk in the school classroom scene.…”
Section: Discussionmentioning
confidence: 99%
“…A less “mentalistic” interpretation could be proposed ( D’Entremont and Seamans, 2007 ), but these results nevertheless highlight children’s motivation for reinstating joint action toward a shared goal. The development of this capacity has received much attention from researchers, as the initiation of joint attention appears to be strongly related to language comprehension and production in the second and third year of life ( Colonnesi et al, 2010 ; Cochet and Byrne, 2016 ), as well as to theory of mind ability (e.g., Charman et al, 2000 ; Milward et al, 2017 ) in both typical and atypical development (e.g., Adamson et al, 2017 ).…”
Section: How Does Communication Develop In the Context Of Social Playmentioning
confidence: 99%